Предмет: Алгебра,
автор: milanazhuchkova34
Упрости выражение:
б) (2x - y)^2 + 7xy =
в) (-0, 4c + b)^2 + 0, 2cb=
r) ( - 2x - y)^2 + 8xy =
помогите пожалуйста
Ответы
Автор ответа:
1
Ответ:
a) (3a+b)²-6ab= (3a)²+ 2*3a*b + b² - 6ab = 9a² + 6ab + b² -6 ab = 9a²+ b²
b) (2x-y)²+7xy= 4x² -4xy +y²+ 7xy = 4x²+3xy +y²
в) (-0,4c+b)²+0,2cb= (b-0,4c)²+0,2cb= b²- 0,8cb + 0,16c²+0,2cb =
= b² -0,6cb+0,16c²
г) (-2x-y)²+8xy = - ( 2x + y)²+ 8xy = - 4x² - 4xy - y² +8xy = - 4x²+4xy - y² =
= 4xy -4x² - y²
Похожие вопросы
Предмет: Английский язык,
автор: tockaiT
Предмет: Русский язык,
автор: danilovaoxs
Предмет: Окружающий мир,
автор: Алинушка111
Предмет: Биология,
автор: scottyznanija96
Предмет: Английский язык,
автор: Знаток023